1986
DOI: 10.1177/000992288602500102
|View full text |Cite
|
Sign up to set email alerts
|

Short Stature as the Major Manifestation of Celiac Disease in Older Children

Abstract: Celiac disease was diagnosed by jejunal biopsy and response to gluten elimination in 11 of 23 children with short stature referred after negative endocrine evaluation. The mean age of the group was 11 years, with a range of 5-16. All had been followed for a mean of 2.5 years at a large pediatric endocrine clinic for the evaluation of growth retardation. Bone age retardation of more than 25 percent of the chronologic age was found in all children. Microcytic anemia and past history of gastrointestinal problems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 12 publications
0
20
0
3
Order By: Relevance
“…The prevalence of CD was higher (35-59%) in the studies 11,[14][15][16][17][18] where either the endocrinal workup had been done and/or the sample was very small. In rest of the studies 10,13,[19][20][21][22][23][24] where the endocrinal causes had not been ruled out in the selected children and/or the sample size was relatively larger, the prevalence reported was lower (1.7-8.3%).…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of CD was higher (35-59%) in the studies 11,[14][15][16][17][18] where either the endocrinal workup had been done and/or the sample was very small. In rest of the studies 10,13,[19][20][21][22][23][24] where the endocrinal causes had not been ruled out in the selected children and/or the sample size was relatively larger, the prevalence reported was lower (1.7-8.3%).…”
Section: Discussionmentioning
confidence: 86%
“…Coeliac disease (CD) is a permanent, genetically determined intolerance to gluten that results in entheropathy and frequent malabsorption in children that may impair final statural growth [4,7,8,27,31,32,43,46]. In fact, after starting a gluten-free diet (GFD), a significant increase in height and weight velocity has been evidenced [5,7,11,13,21,22,30], with weight reaching full catch-up growth in the first year of GFD and height reaching the expected centile after about 2 years [1,42,45].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent reports have demonstrated the existence of certain forms of coeliac disease where the alteration in growth is the most evident clinical manifes tation [2][3][4][5]. At times, these cases are accompanied by hacmatological alterations and mild digestive problems.…”
Section: Introductionmentioning
confidence: 99%
“…However, their results have been discordant; some authors have reported modifications in the secre tion of growth hormone (GH) in response to diverse stim uli [8][9][10], while others have not been able to confirm these results [3,5]. In addition, some studies have re ported that the levels of insulin-like growth factor I (IGF-I) are reduced in this disease state and can be returned to normal with the exclusion of gluten from the diet [II,12].…”
Section: Introductionmentioning
confidence: 99%